SMCP Distress Communication Proficiency and Procedural Accuracy Among Maritime Cadets: A Performance Assessment Study at STIP Jakarta - Tristanti Tristanti; Siska Yoniessa; Giovanni Battista Puteri (Proceeding International Collaborative Conference on Multidisciplinary Science, 2026)
Distress, urgency, and safety communication sequences constitute the highest-stakes domain within the Standard Marine Communication Phrases, demanding the most precise phraseological accuracy and procedural correctness under conditions of maximum operational pressure, yet the degree to which SMCP distress communication training at Indonesian maritime academies produces the proficiency level these stakes require has not been empirically assessed through performance-based measurement. This study measures distress communication proficiency among Nautika cadets at Sekolah Tinggi Ilmu Pelayaran (STIP) Jakarta through oral performance assessment across the principal SMCP distress phraseology categories, supplemented by cadet self-assessment survey and lecturer focus group discussion. Data were collected between April 2025 and April 2026 from 90 Nautika cadets and eight Maritime English and SMCP lecturers. Thematic analysis, cross-group comparison, and narrative synthesis were applied alongside quantitative proficiency analysis. Findings reveal a significant intra-domain proficiency variance: Mayday call initiation and structure achieves substantially higher accuracy than subsequent Mayday relay and Search and Rescue coordination phraseology sequences, indicating that cadet proficiency is concentrated at the instructional entry point of distress communication while the extended procedural sequences governing actual rescue coordination remain underdeveloped. A strong self-assessment overestimation tendency across all distress domains, combined with lecturer-identified scenario exposure insufficiency in curriculum design, provides the study's most actionable cross-group finding. The study establishes a STIP Jakarta-specific distress communication proficiency baseline and provides evidence-grounded curriculum enhancement recommendations.